Orthodoxy Goes Pop: Rock Music and Cultural Hegemony in Serbia - Jovanović, Miloš (Res Facta Nova, 2025)
The paper deals with the symbolic struggles over cultural hegemony in contemporary Serbia. Two rock albums, Одбрана и последњи дани by Idoli (1982), and a compilation Песме изнад истока и запада (2001) have been chosen as case studies. The narratives and discourses contained, as well as those induced by the records, are identified and analysed. Both albums engage with Orthodox Christian motifs and themes. The different socio-political contexts in which they appeared shaped the meanings, together with cultural and political effects they helped produce.